Formulation, optimization, in-vivo biodistribution studies and histopathological safety assessment of duloxetine HCl-loaded ultra-elastic nanovesicles for antidepressant effect after intranasal and transdermal delivery - Radwa M.A. Abd-Elal; Aya M. Essawy; Maha A. Salem; Mahitab Elsayed; Mona G. Khalil; Eman Abdelhakeem; Nouran A. Ali; Mai Ahmed Tawfik (Elsevier, 2023)
Duloxetine hydrochloride (DUL) is a BCS class-II antidepressant drug, acting via serotonin and norepinephrine reuptake inhibition. Despite high oral absorption, DUL suffers limited bioavailability due to extensive gastric and first-pass metabolism. To improve DUL's bioavailability; DUL-loaded elastosomes were developed, via full factorial design, utilizing various span®60: cholesterol ratios, edge activator types and amounts. Entrapment efficiency (E.E.%), particle size (PS), zeta potential (ZP) and in-vitro released percentages after 0.5 h (Q0.5h) and 8 h (Q8h) were evaluated. Optimum elastosomes (DUL-E1) were assessed for morphology, deformability index, drug crystallinity and stability. DUL pharmacokinetics were evaluated in rats following intranasal and transdermal application of DUL-E1 elastosomal gel. DUL-E1 elastosomes [comprising span®60 and cholesterol (1:1) and brij S2 (edge activator; 5 mg)] were optimum with high E.E.% (81.5 ± 3.2%), small PS (432 ± 13.2 nm), ZP (−30.8 ± 3.3 mV), acceptable Q0.5h (15.6 ± 0.9%), and high Q8h (79.3 ± 3.8%). Intranasal and transdermal DUL-E1 elastosomes revealed significantly higher Cmax (251 ± 18.6 and 248 ± 15.9 ng/mL) at Tmax (2 and 4 h) and improved relative bioavailability (≈ 2.8 and 3.1 folds) respectively, in comparison to oral DUL aqueous solution. In-vivo histopathological studies were conducted to ensure the safety of DUL-E1. Elastosomes are promising novel nano-carriers, capable of enhancing the bioavailability of DUL via various routes of administration.